RETRACTED : Analysis of the Effect of Leverage, Profitability, Company Size, Sales Growth and Institutional Ownership on Tax Avoidance (Empirical Study on Manufacturing Companies Registered on BEI 2017-2021) - Bella Sukma Cahyanti; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to examine the Analysis of the Effect of Leverage, Profitability, Firm Size, Sales Growth and Institutional Ownership on Tax Avoidance. The object of this research is a manufacturing company in the consumer goods industry sector (goods consumer industry). The sample used in this study was 115 samples consisting of 23 companies for 5 years. With purposive sampling technique, the method used is multiple regression analysis, classical assumption test and descriptive statistics. The results showed that Leverage had no effect on tax avoidance, Profitability had a positive effect on tax avoidance, Firm size had no effect on tax avoidance, Sales Growth had a negative effect on tax avoidance, Institutional ownership had no effect on tax avoidance.